Small‐molecule inhibition of MuRF1 attenuates skeletal muscle atrophy and dysfunction in cardiac cachexia. Issue 6 (8th September 2017) - Bowen, Thomas Scott; Adams, Volker; Werner, Sarah; Fischer, Tina; Vinke, Paulien; Brogger, Maria Noel; Mangner, Norman; Linke, Axel; Sehr, Peter; Lewis, Joe; Labeit, Dittmar; Gasch, Alexander; et al.
Abstract: Background: Muscle ring finger 1 (MuRF1) is a muscle‐specific ubiquitin E3 ligase activated during clinical conditions associated with skeletal muscle wasting. Yet, there remains a paucity of therapeutic interventions that directly inhibit MuRF1 function, particularly in vivo . The current study, therefore, developed a novel compound targeting the central coiled coil domain of MuRF1 to inhibit muscle wasting in cardiac cachexia. Methods: We identified small molecules that interfere with the MuRF1–titin interaction from a 130 000 compound screen based on Alpha Technology. A subset of nine prioritized compounds were synthesized and administrated during conditions of muscle wasting, that is, to C2C12 muscle cells treated with dexamethasone and to mice treated with monocrotaline to induce cardiac cachexia. Results: The nine selected compounds inhibited MuRF1–titin complexation with IC50 values <25 μM, of which three were found to also inhibit MuRF1 E3 ligase activity, with one further showing low toxicity on cultured myotubes. This last compound, EMBL chemical core ID#704946, also prevented atrophy in myotubes induced by dexamethasone and attenuated fibre atrophy and contractile dysfunction in mice during cardiac cachexia. Proteomic and western blot analyses showed that stress pathways were attenuated by ID#704946 treatment, including down‐regulation of MuRF1 and normalization of proteins associated with apoptosis (BAX) and protein synthesis (elF2B‐delta). Furthermore, actin ubiquitinylation and proteasome activity was attenuated. Conclusions: We identified a novel compound directed to MuRF1's central myofibrillar protein recognition domain. This compound attenuated in vivo muscle wasting and contractile dysfunction in cardiac cachexia by protecting de novo protein synthesis and by down‐regulating apoptosis and ubiquitin‐proteasome‐dependent proteolysis.